Sociodemographic and Behavioral Factors Associated With Hypertension and Depression in 4 Rural Communities in Northern Ghana: A Cross-Sectional Study - Masih A. Babagoli; Dorothy Adu-Amankwah; Engelbert A. Nonterah; Raymond A. Aborigo; Irene Kuwolamo; Khadija R. Jones; Evan E. Alvarez; Carol R. Horowitz; Benedict Weobong; David J. Heller (SAGE Publishing, 2024)
Objectives: The prevalences of hypertension and depression in sub-Saharan Africa are substantial and rising, despite limited data on their sociodemographic and behavioral risk factors and their interactions. We undertook a cross-sectional study in 4 communities in the Upper East Region of Ghana to identify persons with hypertension and depression in the setting of a pilot intervention training local nurses and health volunteers to manage these conditions. Methods: We quantified hypertension and depression prevalence across key sociodemographic factors (age, sex, occupation, education, religion, ethnicity, and community) and behavioral factors (tobacco use, alcohol use, and physical activity) and tested for association by multivariable logistic regression. Results: Hypertension prevalence was higher in older persons (7.6% among 35- to 50-year-olds vs 16.4% among 51- to 70-year-olds) and among those reporting alcohol use (18.9% vs 8.5% between users and nonusers). In multivariable models, only older age (AOR 2.39 [1.02, 5.85]) and residence in the community of Wuru (AOR 7.60 [1.81, 32.96]) were independently associated with hypertension, and residence in Wuru (AOR 23.58 [7.75-78.25]) or Navio (AOR 7.41 [2.30-24.74]) was the only factor independently associated with depression. Conclusions: We report a high prevalence of both diseases overall and in select communities, a trend that requires further research to inform targeted chronic disease interventions.